(untitled) (Bangladesh Journal of Medicine, 2024)
Ifosfamide is an alkylating chemotherapeutic agent that was approved for medical use in the United States in 1987. It is frequently prescribed either alone or in combination with other agents to treat a variety of cancers, such as sarcomas, lymphomas, and lung cancers. It has increasingly been associated with the development of acquired Fanconi Syndrome. Fanconi Syndrome is characterized by the dysfunction of the proximal renal tubule, leading to the inability to reabsorb essential nutrients and electrolytes from the urine. This causes a wide range of abnormalities in electrolyte levels which can lead to a host of metabolic complications if not recognized and efficiently treated. We describe a case of a patient who developed acquired Fanconi Syndrome after starting a chemotherapy regimen with Ifosfamide for a known malignancy. Upon discontinuation of the Ifosfamide and repletion of electrolytes, the patient improved clinically with resolution of renal injury and stabilization of electrolyte levels. This report aims to increase awareness for Fanconi Syndrome and demonstrate the necessity for having high clinical suspicion of this condition, especially when managing patients who are on chemotherapeutic agents, such as Ifosfamide. Bangladesh J Medicine 2024; 35: 200-203